Aspek Sosiologis Dalam hukum Jual Beli - Sulthonuddin, Bung Hijaj; Syaripudin, Enceng Iip (Jurnal Hukum Ekonomi Syariah, 2022)
Buying and selling is an agreement activity in the economy called exchanging objects or goods that have a happy value between the two parties. The implementation of buying and selling by the community requires law as a benchmark to create legal order and solve problems that inevitably arise in buying and selling activities. Sharia Economic Law as a solution in solving various problems that inevitably arise in buying and selling, for example Ghisysy (hiding defects in trading). This study aims to analyze buying and selling in terms of sociological aspects. The formulation of the problem is: what is called sociological, what is called law, and how it relates to sociological aspects of buying and selling law. The method in this writing uses literature study research (Library reseach) and is analyzed using qualitative data analysis techniques through stages: studying, reducing, tabulating, categorizing, and interpreting.